Contested Learning in Welfare Work : A Study of Mind, Political Economy, and the Labour Process / [electronic resource] - Sawchuk, Peter H. (Cambridge : Cambridge University Press, 2013)
Drawing on the field of cultural historical psychology and the sociologies of skill and labour process, Contested Learning in Welfare Work offers a detailed account of the learning lives of state welfare workers in Canada as they cope, accommodate, resist and flounder in times of heightened austerity. Documented through in-depth qualitative and quantitative analysis, Peter Sawchuk shows how the labour process changes workers, and how workers change the labour process, under the pressures of intensified economic conditions, new technologies, changing relations of space and time, and a high-tech version of Taylorism. Sawchuk traces these experiences over a seven-year period that includes major work reorganisation and the recent economic downturn. His analysis examines the dynamics between notions of de-skilling, re-skilling and up-skilling, as workers negotiate occupational learning and changing identities.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Human services; Social service; Civil service; Public administration